Cores and core logging for geoscientists - Blackbourn, Graham A. (Whittles Publishing, 2012)
This Second Edition has been brought up-to-date and incorporates modern developments in coring techniques and core handling. All aspects of cores are covered including cutting and recovery; wellsite handling and logging; recognition of coring damage; laboratory analysis; logging and sampling; preservation and storage. Logging and interpretation are dealt with in detail, encompassing structural and engineering investigations in addition to sedimentology. Emphasis is laid throughout on those features most important to the economical development of geological resources. --